Draft Seventh Five Year Plan 1985-90 and Annual Plan 1985-86 Volume - I An Overview Government of Assam - Planning Commission (Planning Commission, 1985)
Assam is situated in the extreme North Eastern Region of the country. Assam actually forms the core of the North Eastern Region comprising of Arunachal Pradesh, Manipur, Meghalaya, Mizoram, Nagaland and Tripura beside Assam. It has common borders with all the other six units of the Region and also with West Bengal beside international borders with Bangladesh and Bhutan. The entire Region is connected with the rest of India by a slender corridor leading from Dhubri and Kokrajhar districts of Assam.
Planning and Development Department, Government of Assam